A mixed finite element method for the Poisson problem using a biorthogonal system with Raviart–Thomas elements. Issue 3 (21st December 2020) - Banz, Lothar; Ilyas, Muhammad; Lamichhane, Bishnu P.; McLean, William; Stephan, Ernst P.
Abstract: We use a three‐field mixed formulation of the Poisson equation to develop a mixed finite element method using Raviart–Thomas elements. We use a locally constructed biorthogonal system for Raviart–Thomas finite elements to improve the computational efficiency of the approach. We analyze the existence, uniqueness and stability of the discrete problem and show an a priori error estimate. We also develop an a posteriori error estimate for our formulation. Numerical results are presented to demonstrate the performance of our approach.